Cash On Delivery (COD) dalam E-Commerce Perspektif Maslahah - Ummal Khoiriyah (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2023)
Izzuddin's maslahah approach is a maslahah that combines moderate thinking and Sufism. So it is important to discuss the cash on delivery (COD) payment method contract in e-commerce from a maslahah perspective and its implementation to understand the contract and implementation of e-commerce couriers. This problem can be solved using qualitative descriptive research methods. Data can be obtained from interviews and several other sources. To describe courier contracts with the cash-on-delivery payment method in e-commerce by JNE and J&T service companies from the perspective of Maslahah Izzuddin Ibnu Abdissalam. To describe the implementation of courier contracts using the cash-on-delivery payment method in e-commerce by JNE and J&T service companies from Mas}lahah Izzuddin Ibnu Abdissalam's perspective. Based on this data, research findings include COD service contracts and courier responsibilities, transaction status, and relationships between parties. COD service contracts include shirkah, ijarah, and grants. Meanwhile, the courier's responsibility as a consequence of the ijarah contract is yad domanah. Transaction status on COD services is luzum, fasah, and mauquf. For the relationship between parties, the buyer and courier are musta'jir and ajir, the seller and courier are muwakkil and wakil and the relationship between seller and buyer is bai' and mushtary. Based on Izzuddin Ibnu Abdi Salam's maslahah approach, an e-commerce courier contract is an act of creating happiness and enjoyment using jalbu al-masalih wa dar`u al-mafasid which falls into the categories of hajiyat, duniawiy and majaziy